Overeducation and local labour markets in Spain - Raúl Ramos; Esteban Sanromá (European Regional Science Association (ERSA), 2004)
One aspect that has not been widely considered by the literature on the topic is differential overeducation, the existence of differences among men and women in terms of overeducation as a result of the geographical restrictions of married woman when searching for job. In this context, Büchel y Van Ham (2002) have highlighted the relevance of spatial mobility in regional labour markets (basically commuting) as an explanatory factor of women differential overeducation, but also of global overeducation.The objective is this paper is to test the influence of individual variables and some characteristics of regional labour markets related with spatial mobility on overducation in the Spanish Economy. With this aim, we use microdata from the Encuesta de Presupuesto Familiares 1990-91 (Budget Family Survey). The results permits us to conclude that the size of local labour markets and the possibility of increasing the job search to other labour markets through commuting are relevant factors to explain overducation in the Spanish labour market.
Keywords: 330